INTERFERON BETA INHIBITS DENDRITIC CELL MIGRATION THROUGH STAT-1 MEDIATED TRANSCRIPTIONAL SUPPRESSION OF CCR7 AND METALLOPROTEINASE 9 - Yen, Jui-Hung (2010)
Interferon β (IFNβ) is an approved therapeutic option for the treatment of multiple sclerosis (MS). The molecular mechanisms underlying the effects of IFNβ in MS are not fully understood. Migration of dendritic cells (DC) from the inflammatory site to draining lymph nodes for antigen presentation and activation of naïve T cells, and to the CNS for reactivation of encephalitogenic T cells, requires CCR7 and MMP-9 expression. Here we report for the first time that IFNβ inhibits CCR7 expression and MMP-9 production in mature DC, and reduces their migratory capacity. The effect of IFNβ is mediated through STAT-1. In vivo treatment with IFNβ results in lower numbers of DC migrating to the draining lymph node following exposure to FITC, and in reduced expression of CCR7 and MMP-9 in splenic CD11c(+) DC following LPS administration. IFNβ and IFNγ share the same properties in terms of effects on CCR7, MMP-9 and DC migration, but have opposite effects on IL-12 production. In addition, IFNβ-treated DC have a significantly reduced capacity for activating CD4(+) T cells and generating IFNγ-producing Th1 cells. The suppression of mature DC migration through negative regulation of CCR7 and MMP-9 expression represents a novel mechanism for the therapeutic effect of IFNβ.